2020
DOI: 10.1097/md.0000000000022491
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridging—an unusual cause of Wellens syndrome

Abstract: Rationale: Coronary chest pain is usually ischemic in etiology and has various electrocardiographic presentations. Lately, it has been recognized that myocardial bridging (MB) with severe externally mechanical compression of an epicardial coronary artery during systole may result in myocardial ischemia. Such a phenomenon can be associated with chronic angina pectoris, acute coronary syndromes (ACS), coronary spasm, ventricular septal rupture, arrhythmias, exercise-induced atrioventricular conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The prevalence and prognostic implications of Wellens' sign in a contemporary cohort of patients with acute coronary syndromes (ACS) have not yet been elucidated [7]. Systematic review of available data in the literature showed plenty of case reports of WS with particular etiology (in-stent neoatherosclerosis [8], noncritical plaque coronary artery vasospasm [3,9], coronary vasospasm due to illicit drugs use [10], spontaneous coronary artery dissection [11], myocardial bridging [12], coronary fistulae [13], stress cardiomyopathy [14]), or atypical ECG and angiographic localization (inferior [15] or posterior [16] localization), but very few studies. The inventory of the studies published so far in are shown in The prevalence of Wellens' sign in patients with UA in the first study of de Zwaan and Wellens was 18% (26 of 145 patients) [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and prognostic implications of Wellens' sign in a contemporary cohort of patients with acute coronary syndromes (ACS) have not yet been elucidated [7]. Systematic review of available data in the literature showed plenty of case reports of WS with particular etiology (in-stent neoatherosclerosis [8], noncritical plaque coronary artery vasospasm [3,9], coronary vasospasm due to illicit drugs use [10], spontaneous coronary artery dissection [11], myocardial bridging [12], coronary fistulae [13], stress cardiomyopathy [14]), or atypical ECG and angiographic localization (inferior [15] or posterior [16] localization), but very few studies. The inventory of the studies published so far in are shown in The prevalence of Wellens' sign in patients with UA in the first study of de Zwaan and Wellens was 18% (26 of 145 patients) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented common etiologies of Wellens syndrome, including myocardial bridge[ 11 ], Tako-Tsubo cardiomyopathy[ 12 ], pulmonary embolus[ 13 ], and coronary spasm caused by drug abuse[ 14 ]. The pathophysiological mechanism underlying the characteristic T-wave changes in Wellens syndrome is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main angiographic finding of MB is narrowing of the coronary arteries during systole, it has been shown to persist during the diastole period. 1 , 13 , 14 Therefore, severe ischemia may be occurred in patients with MB. Increased heart rate due to different reasons can shorten the diastole time and increase the cardiac oxygen demand.…”
Section: Discussionmentioning
confidence: 99%